Video Mapping as an audiovisual tool to represent traditional clothing (Mayéutica Revista Científica de Humanidades y Artes, 2025)
The video mapping and graphic design are presented in the Fiesta Mayor Latacungueña as key tools to revalue Ecuadorian culture, highlighting both traditional clothing and social context. Through this technique, the rich history and local traditions are visually transmitted, becoming a powerful tool to promote cultural tourism, mestizaje, and national identity. In this context, the study focuses on the clothing of Mama Negra and the Capitán, applying analytical and descriptive methods to unravel their cultural and social meaning. Based on this analysis, totemlike prototypes and 3D animations of the garments were developed, which were used in the video mapping to inn,sovatively spread ancestral traditions.